Mapping Vulnerability and Resilience: Spatial Analysis and Mitigation Strategies for Culturally Based Violence Against Women and Children - Mardliyah, Uswatul; Rais, Lukman; Nikmatul Ula, Siti Nurul; Aina; Taopan, Agnes; Ramli, Umar; Purwanti, Nanik; Nurlela, Andi (European Public & Social Innovation Review, 2026)
Introduction: This study maps vulnerability to violence and resilience mechanisms among women and children in Sorong City, Southwest Papua. Methodology: using a mixed-methods approach with a convergent parallel design. Quantitative data were collected from 696 respondents (348 women and 348 children) and qualitative insights from 5 informants. Results: Violence is spatially concentrated—women face clustered physical harm in urban centers and sexual risks in specific pockets, while children show similar patterns (46.6% physical; 36.8% psychological; 2.3% sexual) and high digital vulnerability (33.0% unsupervised use; 33.6% harmful content; 27.3% cyberbullying; ~40% unaware of reporting), with women’s risk driven by trauma (39.7%), family conflict (45.1%), and home insecurity (39.1%). Discussions: Despite this, women show resilience through decision-making ability (57.2%), recovery capacity (59.2%), and spirituality (≥ 50.9%). Children depend strongly on family support (54.6%). A consistent challenge is limited access to formal services (38.5% of women; 31.9% of children know legal/psychological referral mechanisms). Conclusions: The study recommends integrated mitigation strategies through place-based interventions in urban hotspots, women’s economic empowerment via culturally rooted micro-enterprises, transformation of patriarchal norms, and enhanced child protection in digital spaces—to break the cycle of violence and foster sustainable safety in Sorong City.